Reducing Unnecessary Emergency Department Visits among Cancer Patients - Zribi, Aref; Ayaad, Omar (Asian Pacific Journal of Cancer Nursing, 2025)
Recent studies showed that cancer patients’ visits to emergency departments are rising globally. This can be explained by the growing incidence of cancer and improved survival rates. Cancer patients’ visits to the ED can have detrimental effects that impact both the patients and the overall capability of the healthcare system. Cancer patients constantly need complex care, leading to longer ED stays and higher rates of admission in the hospital, which can strain ED resources and personnel. A significant number of ED visits by cancer patients are considered potentially avoidable. Establishing dedicated oncology outpatient clinics and applying early symptom detection and management pathways can reduce ED visits. Elaborating standardized pathways for controlling frequent symptoms (fever, pain, vomiting) and involving interdisciplinary teams can help manage symptoms in an outpatient clinic, reducing the need for ED visits. This brief communication emphasizes the importance of understanding this phenomenon to improve patient care and resource allocation in healthcare systems.